PENGARUH LEVEL KETINGGIAN AIR TERHADAP EFFISIENSI THERMAL PADA CROSS SECTION WATER TUBE BOILER MENGGUNAKAN GAS DAN SOLAR PRODUKSI SATURATED STEAM PROSES KONTINYU - Saputra, Ardian; Putra, Febbial Pratama; ., Tahdid; Manggala, Agus; ., Zurohaina (Politeknik Negeri Sriwijaya, 2020)
Boilers are used to lower the temperature of the gas and diesel passed through the tubes, and to separate the fluid between the gas phase (water vapor) and the liquid phase (water). In the Boiler water feedback system, a controller is needed that is able to maintain the stability of the water level. The boiler used often has problems that cause less than optimal steam results. The problem that occurs is usually at the level of the water level with the fuel which causes the combustion results to be not optimal and has an impact on the steam produced to be not optimal. Therefore, this research will focus on determining the most appropriate water level with natural gas and diesel fuel so that maximum combustion results are obtained. The tube will also be installed vertically with a slope of 65ËšC with the aim of increasing heat transfer to the boiler and accelerating the evaporation of water molecules which are expected to produce more optimal steam. The parameters observed were temperature, pressure, and the temperature of the combustion flame, the aim was to determine the effect of air on fuel gas and diesel on the speed of temperature and pressure increase. The results of the research show that the optimal water level is the 5th condition (70%) because it can produce saturated steam according to the Efficiency target with a constant state in a continuous process using diesel and gas fuel.